Determination of APTT factor sensitivity – the misguiding guideline. Issue 6 (30th May 2013) - Lawrie, A. S.; Kitchen, S.; Efthymiou, M.; Mackie, I. J.; Machin, S. J.
Summary Introduction The Clinical and Laboratory Standards Institute (CLSI) has produced a guideline detailing how to determine the activated partial thromboplastin time's (APTT) sensitivity to clotting factor deficiencies, by mixing normal and deficient plasmas. Using the guideline, we determined the factor sensitivity of two APTT reagents. Methods APTTs were performed using Actin FS and Actin FSL on a Sysmex CS‐5100 analyser. The quality of factor‐deficient and reference plasmas from three commercial sources was assessed by assaying each of the clotting factors within the plasmas and by performing thrombin generation tests (TGT). Results Testing samples from 50 normal healthy subjects gave a two‐standard deviation range of 21.8–29.2 s for Actin FS and 23.5–29.3 s for Actin FSL. The upper limits of these ranges were subsequently used to determine APTT factor sensitivity. Assay of factor levels within the deficient plasmas demonstrated that they were specifically deficient in a single factor, with most other factors in the range 50–150 iu/dL (Technoclone factor VII‐deficient plasma has 26 iu/dL factor IX). APTTs performed on mixtures of normal and deficient plasmas gave diverse sensitivity to factor deficiencies dependent on the sources of deficient plasma. TGT studies on the deficient plasmas revealed that the potential to generate thrombin was not solely associated with the levels of their component clotting factors. Conclusion Determination of APTT factor sensitivity in accordance with the CLSI guideline can give inconsistent and misleading results.